Peran Orang Tua dalam Menanggulangi Kebiasaan Anak yang Bermain Game Online untuk Meningkatkan Prestasi Belajar Pendidikan Agama Islam di Kelurahan Bakalan Kecamatan Bugul Kidul Kota Pasuruan - Miftakhul Munir; Andik Rizqi (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2022)
This research has a background to reduce children's habits of playing online games by involving the role of parents so that children are not addicted to online games, as well as minimizing the impact it causes in order to improve children's learning achievement. This research was conducted in North Petung Village, Bakalan Subdistrict, Bugul Kidul District, Pasuruan City. To get valid data, the researcher used observation, interview and documentation techniques. Meanwhile, in data analysis, researchers used data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the role of parents in dealing with the habits of children playing online games has played a good role. This role is carried out by taking a good approach to children, for example, such as; 1) discipline the children to play online games at the coffee shop, the wifi is open only until 09: 00 pm 2) set a time limit for playing 3) invite the children to take part in routine activities in the village (reading the maulid diba', recycling waste , routine recitations, hadrah al banjari art) 4) control is always related to the lessons learned while at school 5) accompanying children when studying.